Articulation of the STRUT vowel in L2 English speakers of Swiss German - Gräppi, Christine; Steiner, Carina; Leemann, Adrian (Linguistik Online, 2025)
Given the importance of pronunciation in effective communication, this study investigates Swiss German speakers’ realisation of the English STRUT vowel. Anecdotally, such speakers use this sound more as an open-back vowel. The present study examined 54 students from two different school backgrounds reading out loud. The study involved a comparison of the students’ vowel production with the standard British reference vowels as presented in school textbooks. The findings revealed that male Swiss German speakers produced the STRUT vowel closer to the target than their female counterparts. These results are surprising given that previous research indicated females attain more target-like articulations. In addition, the two school types present a significant effect on the target pronunciation.